2013
DOI: 10.5152/balkanmedj.2013.8125
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Anti-Nuclear Antibody Seroprevalence in Adult Age Groups in Trabzon Province

Abstract: Design -N.K.; Supervision -F.A., M.T.; Resource -N.K., A.A.; Materials -M.T.; Data Collection&/or Processing -N.K., A.A., M.T.; Analysis&/or Interpretation -M.T.; Literature Search -N.K., A.A.; Writing -N.K.; Critical Reviews -M.T., F.A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
2
0
1
Order By: Relevance
“…No statistical differences were found between the ANA and ASMA results in both men and women. This finding is in agreement with other study which reported no association between ANAs and gender 3133, 35,36 . In contrast, other studies reported presence of ANA and/or ASMA to be more predominant in females than in males Current study demonstrates that smoking had no association with ANA and ASMA positivity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…No statistical differences were found between the ANA and ASMA results in both men and women. This finding is in agreement with other study which reported no association between ANAs and gender 3133, 35,36 . In contrast, other studies reported presence of ANA and/or ASMA to be more predominant in females than in males Current study demonstrates that smoking had no association with ANA and ASMA positivity.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, other studies reported presence of ANA and/or ASMA to be more predominant in females than in males Current study demonstrates that smoking had no association with ANA and ASMA positivity. Similar results are reported by other studies.T 30,33,36,38,39 . On the other hand, this finding is in disagreement with Karabulut et al, who reported association between ANAs positivity and smoking 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The highest percentage of positive results was recorded in the age group 30-39 years (16.25%) and the lowest at the age of 70 years and above (12.72%). There was no statistically significant correlation between the presence of ANA and sex, age, place of residence, smoking and BMI [18]. In turn, a study of the Japanese population showed that among the 2,181 studied Anty-LKM 0 0 0 1 p = 0.09; 2 p = 0.81; 3 p = 0.013; 4 p = 0.019; 5 p = 0.35; 6 p = 0.13 people, had a positive ANA -6 of them were diagnosed with Sjögren's syndrome (SS), in 5 Sjögren's syndrome was suspected, and 5 had rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 71%
“…Çalışmalarda kronik ürtikerli çocuk olgularda %0-13,8 arasında değişen oranlarda ANA pozitifliği bildirilmiştir (2,12,23). Türkiye'de sağlıklı erişkin hastalarda ANA pozitifliği %13,2 (1/100 dilüsyon) ve %20,3 (1/80 dilüsyon ve üzeri) bildirilmiştir (24,25). Sağlıklı çocuklarda ise ANA pozitifliği %6-12,6 (1/80 dilasyon ve üzeri) arasında saptanmıştır (26,27).…”
Section: Discussionunclassified